Asuhan Kebidanan Ibu Hamil pada Ny.ꞌꞌWꞌꞌ di Pustu Marinding Kecamatan Bajo Barat Kabupaten Luwu - Jumriana Ibriani; Fitriana Ibrahim; Devianti Tandiallo; Mega Indah (NAJ Nursing Applied Journal, 2024)
Pregnancy is the process of growth and development of an intrauterine fetus starting from conception and ending until the start of labor. The length of pregnancy from ovulation to parturition is around 280 days (40 weeks), and no more than 300 days (43 weeks). This 40 week pregnancy is also called a mature (term) pregnancy. If the pregnancy is more than 43 weeks, it is called postmature pregnancy. Pregnancy between 28 and 36 weeks is called premature pregnancy. The aim of this research is to implement pregnancy midwifery care for Mrs "W" at Pustu Marindik Kec. West Bajo. The care provided uses Varney's 7 Step Midwifery Care Management approach and forms of documentation through SOAP. Case study conducted on Mrs "W". The form of physiologic midwifery care given to Mrs "W" is taking anamnesis on pregnant women, carrying out physical examinations, and providing counseling to pregnant women, regarding personal hygiene, nutrition for pregnant women, adequate rest, and carrying out follow-up. This case study uses a descriptive observational method with a continuity of care approach. The subject is pregnant mother Mrs "W" How to collect anamnesis data, observation, examination and documentation. Next, compare the data obtained with existing theory.